Manajemen Anestesi pada Epilepsi - Prayunanto A.N, Eko; Apsari, Ratih Kumala Fajar; Rahardjo, Sri (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2018)
Epilepsy is a manifestation of brain disorders with a variety of clinical symptoms, caused by the release of electrical charges from brain neurons excessively and periodically, reversibel with various etiology. Seizures can be localized to specific areas of the brain or thoroughly. Focal seizures may expand into generalized seizures. Physiology epilepsy is a disorder defined cerebral balance between excitation and inhibition is the tip of the uncontrolled excitation. Seizures are also caused by potassium conduction abnormalities, ion channel damage, and ATP deficiency associated with ion transport, may cause instability of neuron membranes. The best anesthetic treatment for epilepsy is with general anesthesia. General anesthesia has therapeutic benefits for seizure patients if the patient has been treated with anti-seizure medication then should be continued until surgery.